Retrospective evaluation of risk factors for graft rejection at patients after corneal transplantation performed in Department of Ophthalmology in years 2001-2003 - Kamińska, Anna; Szaflik, Jerzy; Minkiewicz-Timler, Grażyna; Sybilska, Małgorzata; Pawluczyk-Dyjecińska, Martyna; Cieślik, Krzysztof (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
The aim of the study was retrospective evaluation of risk factors for graft rejection in patients after corneal transplantation performed in Department of Ophthalmology in years 2001-2003. 349 cases of penetrating keratoplasty, lamellar, or penetrating with limbal graft, were analyzed. Deep stromal vascularization, anterior synechiae, the use of topical glaucoma medications, previous inflammations in anterior segment of the eye and surgical procedures were evaluated. Period from transplantation to rejection, number of relapses of rejection and changes of visual acuity were also estimated. Corneal graft rejection occurred more frequently in patients with one or more risk factors, particularly deep stromal vascularization, the use of topical glaucoma medications and in young age.